Pendekatan Andragogi Fasilitator Pelatihan Petani Milenial Di Balai Pelatihan Pertanian Sumatera Barat - Annisa Eka Putri; Vevi Sunarti (Jurnal Family Education, 2023)
This research was driven by the excellent academic achievement of the interns, there was an increase in the value of the apprentices, which was influenced by several reasons. One of the reasons considered to be a driving factor for the high learning outcomes of training participants is the instructor's good andragogic approach. This study aims to: 1) Describe the approaches and activities of the androgynous coordinator. 2) Describe the instructor's andragogic approach in providing learning materials. 3) Describe a moderator andragogic approach to using PPDH. 4) Describe the instructor's andragogic approach to managing the learning environment. This study uses a quantitative approach, with a descriptive type which aims to determine the andragogy approach of millennial farmer training facilitators at the West Sumatera Agricultural Training Center. The research population consisted of 60 learning residents and the sampling technique used Stratified Random Sampling and 50% were taken, namely 30 people. The data collection technique uses a questionnaire and the data collection tool is a list of statements, then the data analysis technique uses a percentage formula. The results of the study found that: 1) The andragogical approach of millennial farmer training facilitators at the West Sumatera Agricultural Training Center Based on the Facilitator's Performance Sub-Variables was categorized as good; 2) The andragogic approach of millennial farmer training facilitators at the West Sumatera Agricultural Training Center Based on Learning Material Sub-Variables is categorized as good;3) The andragogical approach of millennial farmer training facilitators at the West Sumatera Agricultural Training Center Based on Learning Method Sub Variables is categorized as good; 4) The andragogical approach of millennial farmer training facilitators at the West Sumatera Agricultural Training Center Based on the Sub-Variables Learning about environmental management is categorized as good. Furthermore, suggestions are expected for future researchers to study new variables in order to be able to reproduce and complement the variables that will be studied further